The impact of chain extender on the properties of polyurethane foam based on rapeseed oil polyol obtained via chemo–enzymatic route. Issue 3 (2nd July 2016) - Kairytė, Agnė; Vaitkus, Saulius; Balčiūnas, Giedrius
Abstract: Presently, researches regarding green chemistry are conducted due to its significance for the mitigation of environmental problems, particularly those related to carbon dioxide emissions in relation to global warming and the usage of fossil feedstocks not only for energy generation but also for materials production. The study examines the impact of bio-products such as corn starch, rapeseed glycerin as well as petroleum based propylene glycol as bifunctional and trifunctional chain extenders on physical-mechanical properties of polyurethane foam from rapeseed oil polyol derived via chemo-enzymatic route. The obtained foams were characterized using European and international methodologies for determination of density, compressive strength perpendicular and parallel to foaming directions, thermal conductivity, long-term water absorption after 28 days of immersion, closed cell content and cell size. Foams containing (5–25) pphp of corn starch display significantly lower values in density and compressive strength as well as cell size compared to the neat polyurethane foam. The greatest compressive strength and the lowest thermal conductivity are obtained for foams with 25 pphp of rapeseed glycerin. All foams extended with bio-products and propylene glycol are characterized by the higher long-term water absorption compared to that of the neat polyurethane foam.